Piloting a Four-Year High School Education Program: Opportunities for Change in Eswatini - Fato, Shepherd; Makamure, Gibson (Universal Education, 2026)
Eswatini embarked on a novel pilot study to find the feasibility of offering a four-year duration in high school rather than the traditional five years. A case study was done in one of the schools in the fourth year of conception. This specifically aimed to establish how the program has been going on now that it was coming to its end. Qualitative data were collected from one principal and four teachers. The findings highlighted how the program was planned, designed, and implemented. Operational challenges like a lack of Ministry support, challenges with resources, staffing, and a negative impact on students were highlighted. Nonetheless, potential opportunities and benefits from this endeavour could include reduced financial burden on the government. It could produce, too, a more robust education system that competes internationally. The study underscores that educational change is a collaborative and inclusive effort that involves many stakeholders. The study thus expands academic understanding of how educational reforms can falter when decision-making neglects infrastructural, instructional, and pedagogical support. We suggest a reflective post-piloting phase as an important step to consider the next step towards a full-scale roll-out in the country.